Video development of napkin folding on food and beverage service subject - Nurhalizah, Siti; Anggraeni, Andian Ari (AIP conference proceedings, 2024)
The video combines audio and visual displays such as text, images, and animation. Video is the preferred learning media for Generation Z students. This study aimed to (1) develop a video of napkin folding for the subject of Food and Beverage Service and (2) determine the feasibility of the video. This study used the R&D (Research and Development) method with a 4D development model (define, design, development, and disseminate). The video discussed several aspects of napkin folding, such as terminology, function, characteristic, type, shape, treatment and care, and making procedure. The animation pictures were created using the Sketchbook application. Napkin folding photos were taken using a Canon EOS 4000 DSLR camera with the help of a ring light. The sound was recorded with the EZVoice application with the help of the Pop Filter tool and edited using Audacity. Video editing was performed using Ms. PowerPoint 2016. The video duration was 7 minutes 40 seconds with mp4 file format and 720p resolution. The video feasibility test was conducted by two material experts, a media expert, and 30 students of class X Culinary at Vocational High School Muhammadiyah 1 Moyudan. The results of the feasibility test concluded that this video was very suitable to be used as a learning medium.